I can sure try mate!!! What is it that you need help with?
Answer:
f(h(-1)) = -1
Step-by-step explanation:
f(x) = (x-4)/3
h(x) = 3x + 4
f(h(-1)) = ?
So first off we need to solve for h(-1):
h(x) = 3x + 4
h(-1) = 3(-1) + 4
h(-1) = 1
Next, we plug this value into the f(x) equation:
f(x) = (x-4)/3
f(1) = (1-4)/3
f(1) = -1
f(h(-1)) may look confusing but it is just f(x) with x being the resulting value for h(-1)
Thus we can say that f(h(-1)) is equal to -1
It's almost solved. Just move the -2 to the other side.
n^2-10n+22=-2
n^2-10n+24 done!
Answer:
72 yellow balls
Step-by-step explanation:
80% of 90 is (0.80*90) = 72 yellow balls.